Coexistence of ferroelectric triclinic phases in highly strained BiFeO3 films - Chen, Zuhuang (2014)
Two tilted triclinic phases were found via synchrotron x-ray diffractions in the mixed-phase regions of highly strained BiFeO3 films. First-principles calculations suggest that these two triclinic phases originate from a phase separation of a single monoclinic state accompanied by elastic matching between the two phase-separated states and further suggest that the ease of phase transition between these two energetically close phases is responsible for the large piezoelectric responses observed in Zhang et al., Nat. Nano. 6, 98 (2011).